Does sharia governance in secular countries exist? Turkey and France experience - M. Hanief Mu'afi; Razali Ade Syahputra Hasibuan (Journal of Islamic Accounting and Finance Research, 2025)
Purpose - This study seeks to answer the question, "does shariah governance exist in secular countries?" by examining Turkey and France as case studies. Method - This study adopts Whittington’s practice theory approach, with Shariah governance indicators carefully prepared. Content analysis is applied to data from regulatory websites, annual reports, and official bank websites in Turkey and France. Each piece of information that aligns with the predefined indicators is systematically compiled, enabling a comparative assessment of shariah governance regulations, structures, processes, and reporting practices across both countries. Result - The study finds that shariah governance in secular countries varies significantly and is influenced by political will and regulatory frameworks. In France, Shariah governance remains undeveloped due to constitutional restrictions on religious intervention. In contrast, Turkey has institutionalized shariah governance, with TKBB issuing regulations and overseeing participation banks, yet weaknesses remain in governance structures and reporting standards. These findings reinforce Institutional Theory, demonstrating how political and regulatory environments shape the effectiveness of Shariah governance in secular states. Implication - The study highlights how regulatory frameworks and political dynamics shape Shariah governance in secular contexts, offering insights for Islamic banks, regulators, and policymakers to strengthen governance to enhance compliance and ensure sustainability. Originality - This is one of the first studies to investigate the existence of sharia governance in a country with a secular constitution and reveal how political dynamics may influence it.